TINGKAT KEMIRIPAN DAN KOMPETISI STRUKTUR EKSPOR KOMODITAS REMPAH-REMPAH INDONESIA DI PASAR INTERNASIONAL - Herdiana Anggrasari; Jangkung Handoyo Mulyo (Universitas Sebelas Maret, 2022)
Economic globalization provides greater opportunities and challenges for the agricultural sector, especially those of spices throughout the world. The commodity does not only need to compete in the outside market, therefore it is in the free market and has an important one. The purpose of this study is 1) to find out the potential and opportunities for the export of Indonesian goods by looking at the level of similarity in the structure of exports and 2) knowing the level of competition with Indonesia and other countries in the International Market. This study uses secondary data obtained from UNComtrade within a period of 15 years (2000-2017). The data used are Vietnamese exports with India, the Netherlands, China and Madagascar. Export of Compatibility Index (ESI) and Export Overlap Index (IEO) to determine the level of similarity and level of competition for spice exports. The results of the study show that 1) Trade in spice commodities between Indonesia and countries that have similarity levels that are looking for decline and 2) competition between Indonesia and consumer countries (below 30). The findings show the potential and opportunities of Indonesian exports in the International Market are still wide open.